Botanicals as Modulators of Neuroplasticity: Focus on BDNF - Enrico Sangiovanni; Paola Brivio; Mario Dell’Agli; Francesca Calabrese (Neural Plasticity)
The involvement of brain-derived neurotrophic factor (BDNF) in different central nervous system (CNS) diseases suggests that this neurotrophin may represent an interesting and reliable therapeutic target. Accordingly, the search for new compounds, also from natural sources, able to modulate BDNF has been increasingly explored. The present review considers the literature on the effects of botanicals on BDNF. Botanicals considered were Bacopa monnieri (L.) Pennell, Coffea arabica L., Crocus sativus L., Eleutherococcus senticosus Maxim., Camellia sinensis (L.) Kuntze (green tea), Ginkgo biloba L., Hypericum perforatum L., Olea europaea L. (olive oil), Panax ginseng C.A. Meyer, Rhodiola rosea L., Salvia miltiorrhiza Bunge, Vitis vinifera L., Withania somnifera (L.) Dunal, and Perilla frutescens (L.) Britton. The effect of the active principles responsible for the efficacy of the extracts is reviewed and discussed as well. The high number of articles published (more than one hundred manuscripts for 14 botanicals) supports the growing interest in the use of natural products as BDNF modulators. The studies reported strengthen the hypothesis that botanicals may be considered useful modulators of BDNF in CNS diseases, without high side effects. Further clinical studies are mandatory to confirm botanicals as preventive agents or as useful adjuvant to the pharmacological treatment.